Planning and Organizing Tahfidz Al-Qur'an Learning at Children's Islamic Boarding Schools - Ma’rifah Ma’rifah; Endang Fauziati; Maryadi Maryadi (Budapest International Research and Critics University, 2023)
Al-Qur'an tahfidz learning is growing rapidly in formal and non-formal education. Management is the most basic thing in the implementation of learning. Planning and organizing are components of management. The purpose of the research is to explain the planning of learning Tahfidz Al-Qur'an. Field study research using qualitative methods, data collection by observation, documentation and interviews. Data analysis by going directly to the field studying, collecting data, compiling and analyzing. Data validity by extending observations and data checking using data and technique triangulation. The results of the study found that: 1) planning was prepared on the halaqoh program with tahfidz grouping carried out when registering new students, the daily program was divided into three times, namely dawn, asar and sunset, the tahsin program was carried out after depositing tahfidz Al-Qur'an, target memorization program with the distribution of thirty juz within six years and ikhtibar program twice a year. 2) Organizing is made up of human resources, namely ustadz tahfidz and class management in the form of a circle.